PENGRUH STRATEGI BELAJAR AKTIF INDEX CARD MATCH (ICM) TERHADAP HASIL BELAJAR MATEMARIKA SISWA KELAS VIII SMP NEGERI 1 KEPENUHAN - -, Alfiana; Deswita, Hera; Afri, Lusi Eka (Universitas Pasir Pengaraian, 2015)
One of active learning strategies is index card match (ICM) the aim of the research is to know whether any influence of ICM active learning toward the result of match learning or not. The method of this research is quasi was applied on experiment class of state junior high school 1 kepenuhan, and conventional learning model was applied on control class. The sampling technigue that is used here is jenuh sampling. The instrument is some multiple choices question that have been analyzed earlier validity, realibility, discriminating capacity and difficulty level. Mean while the hypothesis offered that there is influence of ICM active learning toward learning result. The hypothesis testing uses t-test. The result of calculator was gother tcount = 7.698 and ttable = 2.029. this thing shows that tcount > ttable on the real standard of 5 %. So, there is influence of ICM active learning strategy toward match score